Characterization of a Tospovirus Isolate of Iris Yellow Spot Virus Associated with a Disease in Onion Fields in Brazil - Pozzer, L (Plant disease, 1999)
A tospovirus from onion causing a disease known as "sapeca" by growers in Brazil was characterized. Symptoms on onion consisted of numerous eyelike spots on the leaves and flower stalks resulting in flower abortion. Nicotiana benthamiana and N. rustica were the only systemic hosts experimentally found. Double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) experiments demonstrated that this virus was serologically related to iris yellow spot virus (IYSV), a tospovirus recently described in the Netherlands. This virus, from onion, based on an amino acid sequence identity of 90.5% for the N gene protein, is regarded as a strain of IYSV and is designated IYSVBR This 10% divergence in the nucleocapsid protein may represent an adaptation of the virus to distinct ecological niches